Excelling in Student Achievements (EXCELLA) Real-Time Based on Student Achievement Management Innovation Integrated with Blockchain Systems - Hardita, Putu Restu; Widiarta, I Gusti Komang Agus Angga Putra; Antara, I Gede Wahyu Suwela (LPPM Undiksha, 2024)
Indonesia, which has significant human resources, needs better human resources. The efforts made by the government through the Independent Curriculum program, in fact, still need to be in line with expectations. Many students' potential has yet to be maximized, so innovation is needed to improve the quality of students through competitions and maximizing potential. This research aims to maximize students' potential and improve the quality of human resources in Indonesia. This type of research is qualitative, using quantitative research methods and t-test analysis. The research subjects were 60 students. The methods used to collect data are interviews, observations, and tests. The instrument used to collect data is test questions. Inference analysis was carried out using a Paired Sample T-Test. The Paired Sample T-Test results show a significant difference between the average achievement of students in the experimental group that uses the EXCELLA system and the control group that follows regular learning. The findings of this research have proven to have a positive impact on increasing student achievement and potential. This research implies that EXCELLA has excellent potential to become a practical learning innovation in improving the quality of Indonesian human resources. With continued support from the government and other stakeholders, EXCELLA can significantly create a superior and competitive future generation.